Defense of Elevated Body Weight Setpoint in Diet-Induced Obese Rats on Low Energy Diet Is Mediated by Loss of Melanocortin Sensitivity in the Paraventricular Hypothalamic Nucleus - Luchtman, Dirk W.; Chee, Melissa J. S.; Doslikova, Barbora; Marks, Daniel L.; Baracos, Vickie E.; Colmers, William F. (PLOS ONE, 2015)
Some animals and humans fed a high-energy diet (HED) are diet-resistant (DR), remaining as lean as individuals who were naïve to HED. Other individuals become obese during HED exposure and subsequently defend the obese weight (Diet-Induced Obesity- Defenders, DIO-D) even when subsequently maintained on a low-energy diet. We hypothesized that the body weight setpoint of the DIO-D phenotype resides in the hypothalamic paraventricular nucleus (PVN), where anorexigenic melanocortins, including melanotan II (MTII), increase presynaptic GABA release, and the orexigenic neuropeptide Y (NPY) inhibits it. After prolonged return to low-energy diet, GABA inputs to PVN neurons from DIO-D rats exhibited highly attenuated responses to MTII compared with those from DR and HED-naïve rats. In DIO-D rats, melanocortin-4 receptor expression was significantly reduced in dorsomedial hypothalamus, a major source of GABA input to PVN. Unlike melanocortin responses, NPY actions in PVN of DIO-D rats were unchanged, but were reduced in neurons of the ventromedial hypothalamic nucleus; in PVN of DR rats, NPY responses were paradoxically increased. MTII-sensitivity was restored in DIO-D rats by several weeks’ refeeding with HED. The loss of melanocortin sensitivity restricted to PVN of DIO-D animals, and its restoration upon prolonged refeeding with HED suggest that their melanocortin systems retain the ability to up- and downregulate around their elevated body weight setpoint in response to longer-term changes in dietary energy density. These properties are consistent with a mechanism of body weight setpoint.